Works Printed in Vilnius in the Eighteenth-Century Manuscript Catalogue of the Vilnius Jesuit Academy Library - Rinkūnaitė, Aušra (Senoji Lietuvos literatūra, 2024)
Based on the eighteenth-century manuscript catalogue of the Vilnius Jesuit Academy library, the purpose of the article was to investigate what part of the library consisted of the output of the printing houses of Vilnius, to identify the printers of Vilnius whose output the library had and the number of those works, and the themes of books that the Jesuits read.From approximately 4500 entries in the catalogue, 155 entries were selected in which Vilnius was indicated as the place of publication or identified as such. All the information, including transcribed catalogue entries, identified publications, books belonging to the Vilnius Jesuit Academy library with their provenance marks and the current known location of their storage, is provided separately in the appendix. During the research, 143 titles were identified, and 259 copies were counted. After identifying almost all the printed works selected from the catalogue, it turned out that the library had eight titles (nine copies) printed in the sixteenth century, 68 titles (122 copies) from the seventeenth century, and 67 titles (128 copies) printed in the eighteenth century. Most of them were the output of the Vilnius Academy printing house. Religious texts, comprising polemical, hagiographic, and theological writings, constituted 56 per cent of all printed works, while works on logics, mathematics, geography, and physics made up only 7.7 per cent. Various calendars started to be printed in the second half of the eighteenth century and became very popular. The largest number of works printed in Vilnius were in Latin (48.6 per cent) and Polish (47.2 per cent); works in French, German, Lithuanian, Latvian, and other languages accounted for 4.2 per cent. The inscriptions in the books reveal that the Jesuits not only bought books but also received them as gifts. Not only famous patrons but also the authors such as Maciej Miłuński, Jan Zrzelski, Antonius Aloysius Misztołt donated books to the library. The Vilnius Academy printing house also donated several books. Thus, the manuscript catalogue of the Vilnius Jesuit Academy library is a particularly valuable source for researching the history of the Vilnius University library in the eighteenth century. The printed works recorded in it point to the Jesuits’ areas of interest, and the surviving books reveal the history of books entering the library and their wanderings through the libraries of various European countries.
Keywords: manuscript catalogue of the Vilnius Jesuit Academy library; output of the Vilnius Academy printing house; sixteenth-eighteenth-century works printed in Vilnius